Intercultural prejudices and misconceptions in portuguese school books - Prata Gomes, Miguel (2016)
In this paper we want to analyze the intercultural values included in some Portuguese school books. We will show/analyze some prejudices and misconceptions as well as good examples of excellent intercultural education practices in these manuals.